2010
DOI: 10.1097/tp.0b013e3181e641f8
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric En Bloc Kidney Transplantation to Adult Recipients: More Than Suboptimal?

Abstract: EBK had the best long-term outcomes among deceased donor transplants and offer unique options for adult kidney transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 51 publications
2
71
1
Order By: Relevance
“…While early reports of increased vascular complications with en bloc transplantation were discouraging [14][15][16][17], recent reports have shown more encouraging outcomes [4,[18][19][20], further confirmed by our study findings. This is likely due to increased experience and improvements in surgical techniques over time, which should help further reduce the skepticism in using young donor kidneys for transplantation.…”
Section: Other Benefits Of En Bloc Transplantssupporting
confidence: 81%
“…While early reports of increased vascular complications with en bloc transplantation were discouraging [14][15][16][17], recent reports have shown more encouraging outcomes [4,[18][19][20], further confirmed by our study findings. This is likely due to increased experience and improvements in surgical techniques over time, which should help further reduce the skepticism in using young donor kidneys for transplantation.…”
Section: Other Benefits Of En Bloc Transplantssupporting
confidence: 81%
“…[4][5][6] Multiple studies have demonstrated that en bloc kidney transplants from pediatric donors to both adult and pediatric recipients have good clinical outcomes, including long-term graft survival and reduced rates of delayed graft function. [7][8][9][10][11] Recent studies have shown good clinical outcomes with very small pediatric donors. 6,12 Successful en bloc kidney transplantation from newborn and infant donors into both adult and pediatric recipients has recently been reported.…”
mentioning
confidence: 99%
“…While early reports of increased vascular complications with en bloc transplantation were discouraging [27][28][29][30], recent reports have shown more encouraging outcomes [5,11,26,31]. This is likely due to increased experience and improvements in surgical techniques over time, which should help further reduce the skepticism in using young donors for transplantation.…”
Section: Advantages Of En Bloc Over Solitary Grafts From Young or Idementioning
confidence: 95%
“…The graft survival of en bloc kidneys has been at least comparable to standard deceased donor kidneys [4,[8][9][10][11][12]. Some studies in fact have shown superior outcomes with en bloc transplants compared to standard deceased donor and even live donor transplants [13][14][15].…”
Section: En Bloc Renal Transplantation Is a Viable And Safe Option Tomentioning
confidence: 99%